2015
DOI: 10.1016/bs.ircmb.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Unfolded Protein Response, and Apoptosis in Developmental Toxicity

Abstract: Physiological development requires precise spatiotemporal regulation of cellular and molecular processes. Disruption of these key events can generate developmental toxicity in the form of teratogenesis or mortality. The mechanism behind many developmental toxicants remains unknown. While recent work has focused on the unfolded protein response (UPR), oxidative stress, and apoptosis in the pathogenesis of disease, few studies have addressed their relationship in developmental toxicity. Redox regulation, UPR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 312 publications
(379 reference statements)
2
52
0
3
Order By: Relevance
“…Oxidative stress caused by reactive oxygen species (ROS) is an important part of cell apoptosis (29,30). Previous studies have demonstrated that oxidative stress injury is activated in vitiligo (25,31).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress caused by reactive oxygen species (ROS) is an important part of cell apoptosis (29,30). Previous studies have demonstrated that oxidative stress injury is activated in vitiligo (25,31).…”
Section: Discussionmentioning
confidence: 99%
“…ERS and oxidative stress are closely related in many physiological and pathological conditions (21). Protein misfolding in ERS conditions results in reactive oxygen species production, and oxidative stress disturbs the ER redox state and promotes protein misfolding (22). Therefore, the authors hypothesized that ERS may also play an important role in the harmful effects of IS.…”
Section: Discussionmentioning
confidence: 99%
“…These reactive oxygen species can cause DNA strand breakage or fragmentation leading to cell mutation. The importance of oxidative stress as a mechanism of teratogenesis is suggested by several animal studies (Kupsco et al, 2015).…”
Section: Discussionmentioning
confidence: 99%